Evaluation of coagulopathies in acute promyelocytic leukemia at diagnosis and after complete remission by D-dimer titration - خضور, مازن; سعيد, روز (Latakia University Journal -Medical Sciences Series, 2022)
Background: Early hemorrhagic deaths is the most important cause of fatality in acute promyelocytic leukemia. All trans retinoic acid has an important role to induce hematological remission and decrease the coagulopathies that accompanies acute promyelocytic leukemia. Aim: to assess the efficacy of all trans retinoic acid on coagulation profile when complete hematological remission is achieved. Materials and Methods: blood sample were collected from acute promyelocytic leukemia patients at diagnosis and at complete hematological remission. Results: 25 patients were admission in Tishreen University hospital and were treated with all trans retinoic acid, idarubicin and supportive care to maintain a reasonable platelet count. 88% of patients achieved complete hematological remission. Two patients died during induction therapy due to intracranial hemorrhages. All trans retinoic acid was able to normalize coagulation parameters at remission with D-dimer being the most affected parameters of them all. This result emphasizes on the important of D-dimer titration to monitor the coagulopathies and treatment in acute promyelocytic leukemia.